Studies of Alpha2-Adrenergic Receptors of Intact and Functional Washed Human Platelets by Binding of 3H-Dihydroergocryptine and 3H-Yohimbine-Correlation of 3H-Yohimbine Binding with the Potentiation by Adrenaline of ADP-Induced Aggregation - Lanza, François; Cazenave, Jean-Pierre (Thrombosis and Haemostasis, 1985)
The binding of 3H-dihydroergocryptine and 3H-yohimbine to intact, discoid, functional, washed human platelets resuspended in Tyrode’s buffer containing Ca2+, Mg2+, human albumin and apyrase, was studied at 37° C. The binding of 3H-dihydroergocryptine was rapid, reversible and saturable (KD = 19.3 ± 4.2 nM, Bmax = 2590 ± 670 sites per platelet). The results were difficult to interpret because the bound ligand was not easily dissociated. In contrast, 3H-yohimbine bound in a rapid, reversible and saturable fashion to one class of sites (KD = 8.1 ± 1 nM, Bmax = 395 ± 35 sites/platelet) with the characteristics of alpha2-adrenergic receptors. Adrenaline alone did not aggregate intact platelets but potentiated ADP-induced aggregation. This effect of adrenaline was specifically inhibited by alpha2-antagonists such as yohimbine. The inhibition of 3H-yohimbine binding and the inhibition of the synergistic effect of adrenaline on ADP-induced aggregation by 16 different alpha- and beta-adrenergic compounds was significantly correlated (p <0.001). Thus, intact and functional washed human platelets can be used as a simple pharmacological model to screen alpha-adrenergic antagonists by measuring the inhibition of the potentiation of ADP-induced aggregation by adrenaline which is a direct reflection of the physiological effect of adrenaline on human platelet alpha2-adrenergic receptors. The inhibition constant derived from aggregation studies expresses the affinity of the ligand for its receptor as measured by more cumbersome binding studies with radioactive adrenergic antagonists such as 3H-yohimbine.
Keywords: Platelet; Alpha adrenergic receptor; Aggregation; Adrenaline; ADP; Yohimbine; Dihydroergocryptine